Diversidad y distribución potencial de coleópteros coprófagos (Scarabaeidae: Scarabaeinae) bajo escenarios de cambio climático en un gradiente altitudinal de la parroquia El Dorado de Cascales, Sucumbíos-Ecuador - Quinatoa Prado, Rogelio Fernando (2015)
Climate change is due to anthropogenic (95%) and natural (5%) causes, and just like deforestation, it`s one of the main drivers of biodiversity loss. In this research, the potential distribution of 22 dung beetles species as bioindicators was studied, eight of these (Canthon aequinoctialis, Deltochilum amazonicum, Dichotomius podalirius, Dichotomius problematicus, Eurysternus caribaeus, Eurysternus cayennensis, Eurysternus foedus, Ontherus diabolicus) present a reduction, to the point that they could become extinct in Sucumbíos province under RCP6.0 scenario (Representative Concentration Pathways 6.0 Wm-2) by the year 2050. All the models are highly significant (p <0.01) with AUC (Area Under a Receiver Operating Characteristic (ROC) Curve) greater than 0.9, indicating that predictions were better than those obtained at random. Environmental variables with the greatest contribution in the models were precipitation of colder quarter (bio19) and precipitation of driest month (bio14). 3751 individuals belonging to 65 species were captured, representing 23% of the species reported for the country. The analysis of variance showed that the richness and abundance don`t show significant differences between altitudinal strata, and the Kruskal-Wallis determined that there are significant differences in the richness and abundance between different habitats and lures. By using Chao1, the species accumulation curves were highly representative for the altitudinal strata (> 82%). Possible solutions that would improve their adaptability to the effects of climate change are: protected areas network, biological corridors, agroforestry systems and ecosystem approach.